PENGARUH JUMLAH ROKOK YANG DIHISAP SETIAP HARI TERHADAP PENYAKIT KANKER PARU-PARU PADA MAHASISWA SEKOLAH TINGGI ILMU EKONOMI BALI INTERNATIONAL INSTITUTE OF TOURISM MANAGEMENT (STIE –BITTM) SAHID. - Kadek Jemmy Waciko (Soshum: Jurnal Sosial dan Humaniora, 2014)
The purpose of this study is to determine whether there is influence of the number of cigarettes smoked per day against Lung Cancer at the School of Economics student Bali International Institute of Tourism Management (STIE - BITTM) Sahid. After analyzing gradually acquired sig . = 0.403 > 0.05 so that Ho is accepted in other words , a variable number of cigarettes smoked per day did not significantly influence the lung cancer illness among students . Obtained an average value of covariates (which is used as a predictor ) is 5.167 . This value means that both male and female students , the average cigarette rod 5 a day , the students in this study were categorized as light smokers because smoking less than 10 cigarettes per day . In other words they are in the maintenance stage of smoking . For students , smoking is one of self-regulation (self - preparatory ) , smoking was done to obtain unpleasant physiological effects . Based on Plot Survival Function at mean of covariates obtained survival rate (healthy) decreases student active smokers among female respondents in week 7 and men at week 9 through week 12 . This is consistent with the results Plot Hazard Function at Mean of covariates where possible dangers for female respondents lung disease appear after 7th week and continue to increase until week 11 . While for men take place in week 9 and continue to increase up to week 11 . In fact females is getting more possible in having lung cancer than males.